Ultrasound‐based criteria for adequate peripheral venous access in therapeutic apheresis procedures. Issue 6 (4th August 2021) - Salazar, Eric; Gowani, Faaria; Segura, Francisco; Passe, Heather; Seamster, Lamesha; Chapman, Bettie; Joubert, Felicia; Hopson, Stephanie; Easley, Tracy; Garcia, Salvador; Miguel, Robin; Medina, Cindia; et al.
Abstract: Background: Apheresis procedures require adequate vascular access to achieve adequate inlet flow rates. Central dialysis‐type catheters are often used in apheresis, despite their multiple risks. Peripheral venous access is a safe and effective option for many patients. Aim: We previously demonstrated that ultrasound guidance reduces central venous catheter use in apheresis patients; however, no validated criteria for preprocedural evaluation of peripheral veins exist. Here, we hypothesized that ultrasound‐based criteria could predict the adequacy of a peripheral vein for apheresis procedures. Patients/Methods: In this pilot cohort study, we reviewed the procedural outcomes for 50 cases of peripheral venous procedures that used our ultrasound‐based criteria. Results: Of the procedures that met our criteria, 96% (46/48) were successfully completed. Overall, our criteria had 100% sensitivity, 50% specificity, 96% positive predictive value, and 100% negative predictive value. Conclusion: Our criteria justify an evidence‐based ultrasound‐guided standard for evaluation of peripheral venous access for apheresis procedures.